The Effect of Emotional Regulation Training on Emotional Labor and Work Engagement Among Nurses - Hartika, Listiyani Dewi (ANIMA Indonesian Psychological Journal, 2011)
Monotonous job routine, the requirement to express only positive emotions (”display rules”),inequality nurse to patient ration, and inadequate emotion regulation skills are factors thatcontribute to decreased work engagement among nurses. It was hypothesized that the appli-cation of emotional regulation training will facilitate nurses to obtain greater efficacy to enactdeep acting and surface acting. When these goals skills are obtained, nurses will likely be able toincrease their work engagement. The author applied purposive sampling strategy to screen 60nurses as research participants. The author used questionnaires and quasi-experiment researchdesign to categorize participants into two groups. Data was analyzed using Kendall correlation,t-test, and measurement of effect size. Results revealed significant differences between controlgroup’s work engagement posttest scores and experimental group’s WE posttest scores. Theauthor concludes that emotional regulation training have improved the nurses capability to enactdeep acting and also greater work engagement. Pekerjaan yang monoton, adanya display rules dalam bekerja, tidak berimbangnya jumlahperawat dalam menghadapi jumlah pasien yang banyak, kurangnya kemampuan untukmengelola emosi secara efisien merupakan faktor-faktor yang menyebabkan keterikatan kerja(work engagement) perawat terhadap pekerjaannya menjadi kurang optimal. Melalui programemotional regulation training diharapkan perawat lebih mampu melakukan deep acting (DA)ataupun surface acting (SA) secara lebih efisien sehingga perawat mampu meningkatkan workengagement-nya terhadap pekerjaanya. Melalui purposive sampling diperoleh 60 orang perawatsebagai subjek. Melalui survei dan kuasi-eksperimen didesain dua kelompok pra-uji-treatment-pasca-uji . Data dianalisis dengan uji korelasi Kendall, uji beda t-test, serta perhitungan effectsize. Hasil menunjukkan perbedaan yang signifikan antara hasil pasca-uji kelompok kontrol dankelompok eksperimen pada variabel work engagement. Artinya emotional regulation traningmemengaruhi tingkat deep acting dan surface acting perawat yang pada akhirnya berdampakjuga pada meningkatnya tingkat work engagement (WE) perawat terhadap pekerjaanya.